Analysis of the pathogenicity and pathological characteristics of NOTCH3 gene-sparing cysteine mutations in vitro and in vivo models - Gong, Zhenping; Wang, Wan; Zhao, Ying; Wang, Yadan; Sun, Ruihua; Zhang, Haohan; Wang, Fengyu; Lu, Yaru; Zhang, Jiewen (Frontiers in Molecular Neuroscience, 2024)
BackgroundCerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is one of the most common inherited cerebral small vessel diseases caused by the NOTCH3 gene mutation. This mutation leads to the accumulation of NOTCH3 extracellular domain protein (NOTCH3ECD) into the cerebral arterioles, causing recurrent stroke, white matter lesions, and cognitive impairment. With the development of gene sequencing technology, cysteine-sparing mutations can also cause CADASIL disease, however, the pathogenicity and pathogenic mechanisms of cysteine-sparing mutations remain controversial.ObjectiveTo analyze the pathogenicity and pathological features of cysteine-sparing mutations in both in vitro and in vivo mouse models.MethodsA cysteine-sparing mutant of NOTCH3ECD R75Q was constructed by lentiviral transfection in vitro, and the NOTCH3 R75Q knock-in mouse model was constructed by CRISPR/Cas-mediated genome engineering in vivo. A cycloheximide pulse-chase experiment was used to analyze the degradation of NOTCH3 extracellular domain proteins, and the deposition characteristics of NOTCH3ECD were quantitatively analyzed by immunohistochemical staining. The characteristics of the smooth muscle cells and granular osmiophilic materials were observed using electron microscopy.ResultsWe elucidated that the NOTCH3 R75Q mutation is pathogenic. NOTCH3ECD R75Q was found to be resistant to protein degradation and more likely to cause abnormal aggregation of NOTCH3ECD, resulting in reduced cell activity in vitro. The NOTCH3 R75Q mouse model showed pathological characteristics of CADASIL, with age-dependent NOTCH3ECD, granular osmiophilic material, and degenerated smooth muscle cells detected in the brain.ConclusionTo our knowledge, this is the first study to analyze the pathogenicity of NOTCH3 R75Q cysteine-sparing mutations in both in vitro and in vivo models. We demonstrate that NOTCH3ECD induced by NOTCH3 R75Q mutation has toxic effects on cells and reveal the deposition characteristics of NOTCH3ECD in the brain. This provides a feasible model and lays the foundation for further studies on the pathogenesis and therapeutic strategies of NOTCH3 cysteine-sparing mutations.